ANALISIS RASIO KEUANGAN DENGAN METODE ALTMAN Z-SCORE DAN SPRINGATE UNTUK MEMPREDIKSI KEBANGKRUTAN PADA PT SOUTHERN TRISTAR TAHUN 2012 – 2016. - Hayuningtyas Pramesti Dewi; Ilham Fadilah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
This study attempts to calculate the financial ratios formulated in the bankruptcy test model using the Altman Z-Score and Springate methods to analyze the bankruptcy rate at PT Southern Tristar for the 2012-2016 period. Secondary data is processed and discussed descriptively. The results of this study indicate that PT Southern Tristar generally experienced bankruptcy in the period 2012-2016 using both the Altman Z-Score method and the Springate method.